Double-Balloon Enteroscopy-detected Lipid Islets in the Small Bowel are Strong Predictors of Cardiovascular Disease when associated with Angiectasia and Bleeding - Albrecht, Heinz; Hagel, Wolfgang H.; Hagel, Alexander; Neurath, Markus; Raithel, Martin (Journal of Gastrointestinal and Liver Diseases, 2016)
Double-balloon enteroscopy (DBE) is a sensitive and safe procedure for the detection and treatment of mid-gastrointestinal bleeding (MGIB). It combines the possibility of a panenteroscopy with the immediate chance for intervention. This study evaluates the yield of DBE for the detection and treatment of MGIB in an unselected patient cohort.In a five-year period a total of 119 DBEs were carried out on 62 patients due to MGIB. Inclusion criteria were hematochezia, melena, anemia, positive hemoccult-test and iron deficiency. All pre-existing diseases or comorbidities were evaluated. Two main statistical methodologies were used in data analysis: descriptive statistics to describe the basic features of our data and Fisher's exact test for comparisons of proportions.The diagnostic yield was 69% (pathological findings in 43/62 patients) and the main diagnoses in all DBE-procedures were angiodysplasia (22%, 26/119 DBE), followed by lipid islets (18%, 21/119 DBE). In all patients with lipid islets this diagnosis was significantly connected with cardiovascular diseases. The combination of lipid islets and a relevant bleeding source appeared in 79% of the 19 patients with these findings. Of these, 53% had to be treated due to the bleeding event. The overall therapeutic intervention rate was 58%. Serious complications such as perforation or pancreatitis did not occur.Double-balloon enteroscopy as the gold standard for small bowel investigation in MGIB confirmed its high diagnostic yield in an unselected cohort of patients. A new strong combination of lipid islets with cardiovascular disease was revealed, with a high incidence of angiectasia bleeding. This combination should be evaluated in more detail as a new risk factor for MGIB, and should be regarded in this population when therapeutic anticoagulation is needed.
EVALuna2:2076